2022
DOI: 10.2147/copd.s342220
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled Corticosteroid Use Among COPD Patients in Primary Care in Spain

Abstract: Purpose Inhaled corticosteroids (ICS) are frequently used to treat chronic obstructive pulmonary disease (COPD) outside the current recommendations. Our aim was to describe ICS use in COPD patients and to identify factors associated with ICS use among COPD patients treated within primary care in Spain. Patients and Methods This was a cross-sectional, non-interventional and multicenter study of patients with COPD treated in primary care. Patient characteristics and exace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Patients with COPD handled entirely by their PCP are invisible to us via registers because they do not have a registered ICD-10 diagnosis code. These are likely the patients with mild disease and therefore not in ICS treatment [47,52,73]: a recent study has shown that about 32% of patients with COPD in Denmark handled only by their PCP were in ICS treatment, which is considerably lower than in our study [74]. The severity threshold for COPD hospital admission and ICD-10 code registration has increased during our study period [75], which would further increase this potential bias over time.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Patients with COPD handled entirely by their PCP are invisible to us via registers because they do not have a registered ICD-10 diagnosis code. These are likely the patients with mild disease and therefore not in ICS treatment [47,52,73]: a recent study has shown that about 32% of patients with COPD in Denmark handled only by their PCP were in ICS treatment, which is considerably lower than in our study [74]. The severity threshold for COPD hospital admission and ICD-10 code registration has increased during our study period [75], which would further increase this potential bias over time.…”
Section: Discussionmentioning
confidence: 68%
“…One thing, however, is the publication of guidelines, but whether these guidelines are followed is another issue. Studies in the last decade have revealed a high use of ICS by both primary care practitioners (PCP) [47][48][49][50][51] and pulmonary specialists [34,[51][52][53]. Although some studies have indicated a prescription pattern in accordance with treatment guidelines [54,55], most studies have mainly focused on poor adherence to guidelines [48,51,52,[56][57][58].…”
Section: Discussionmentioning
confidence: 99%
“…24 In another primary care study from Spain, almost half (48%) were treated with ICS, although only 27% experienced moderate or severe exacerbations in the previous year (34% during the previous 2 years). 25 A number of observational/registry studies have also been conducted in Japan. [31][32][33][34] Analysis of data from patients with COPD in the COPD Assessment in Practice (CAP) study, 65% of whom had no previous exacerbations in the last year, 31 showed that 28% of patients were treated with LABA/LAMA/ICS and 21% with LABA/ LAMA.…”
Section: Data From Registries: How Are Patients Being Treated In Real...mentioning
confidence: 99%
“…24 In another primary care study from Spain, almost half (48%) were treated with ICS, although only 27% experienced moderate or severe exacerbations in the previous year (34% during the previous 2 years). 25…”
Section: Data From Registries: How Are Patients Being Treated In Real...mentioning
confidence: 99%
See 1 more Smart Citation